Effects of intermittent pneumatic compression on delayed onset muscle soreness (DOMS) in long distance runners - Draper, S.; Kullman, E.; Sparks, K. E.; Little, K. D.; Thoman, J. (International Journal of Exercise Science, 2020)
International Journal of Exercise Science 13(2): 75-86, 2020. The purpose of this study was to observe the effectiveness of intermittent pneumatic compression (IPC) on reducing C-reactive protein (CRP) and DOMS after long distance running.Ten distance runners, five males and five females, ages 20-53 years performed two 20-mile runs at 70% VO2max. Each run was followed by either no treatment (control) or IPC treatment for five consecutive days. For the IPC run, participants were treated for one hour immediately following the run and daily for five more days thereafter. On control runs, participants did not receive any treatment. Serum CRP was measured pre- and post-run, and daily thereafter for five days for both trials. Results indicated no significant difference (p > 0.05) between control and treatment runs in CRP levels. Subjective pain ratings indicated no significant difference in pain between control and treatment runs. In conclusion, there appear to be no substantial benefits of IPC in promoting recovery.